MANAJEMEN PENDIDIKAN ISLAM DALAM PENINGKATAN KEDISIPLINAN SANTRI PONDOK PESANTREN AL-HASAN KAWASEN BANJARSARI CIAMIS JAWA BARAT - Laeliah (UNISAN JURNAL, 2024)
This research aims to examine the role of caregivers and teachers in improving the discipline of students at the Al-Hasan Kawasen Banjarsari Islamic Boarding School. The research method used is qualitative with a case study approach. Data was collected through participant observation, in-depth interviews, and analysis of related documents. The respondents for this research consisted of caregivers, teachers and students at the Al-Hasan Kawasen Banjarsari Islamic Boarding School. The research results show that caregivers and teachers have a very important role in shaping student discipline. They not only act as educators, but also as role models and mentors for the students. Discipline development is carried out on an ongoing basis through consistent application of rules, providing motivation and positive encouragement, as well as personal coaching. Caregivers and teachers also have a role in improving relationships between caregivers, teachers and students. Good communication and mutual understanding are very important in creating a conducive learning environment. With good relationships, disciplinary problems can be identified and resolved more effectively. Implementation of Islamic education management strategies has also proven effective in improving student discipline. Forming a culture of discipline, increasing understanding, strengthening the role of caregivers and teachers, preparing coaching programs, and strengthening communication relationships are the keys to creating a disciplined Islamic boarding school environment. Thus, this research provides an important contribution to understanding the role of caregivers and teachers in improving the discipline of students at the Al-Hasan Kawasen Banjarsari Islamic Boarding School. By paying attention to the factors that have been identified, it is hoped that student discipline can continue to be improved so that Islamic boarding schools can better achieve their Islamic education goals. Keywords: